Autoimmune Encephalitis Associated with Endocrine Dysfunction: A Case Report - Marszał, Wiktoria; Czyż, Sandra (Journal of Education, Health and Sport, 2026)
Autoimmune encephalitis is a rare immune-mediated neurological disorder characterized by brain inflammation associated with autoantibodies targeting neuronal surface or synaptic antigens. It frequently presents with rapidly progressive psychiatric symptoms, cognitive impairment, seizures, and autonomic instability, often mimicking primary psychiatric or infectious conditions. The disease course may be further complicated by concomitant endocrine dysfunction, requiring interdisciplinary management. We report the case of an 18-year-old woman with a history of autoimmune encephalitis and secondary hormonal abnormalities who developed recurrent psychotic decompensation. At the age of 15, she was hospitalized due to acute behavioral deterioration, hallucinations, confusion, and autonomic symptoms. Diagnostic evaluation revealed influenza A infection and inflammatory-demyelinating lesions in the corpus callosum and left cerebral hemisphere on MRI. Laboratory findings showed elevated antithyroid antibodies and hypothalamic amenorrhea, confirming endocrine involvement. Combined antiviral, immunomodulatory, and corticosteroid therapy resulted in significant clinical and radiological improvement. After two years of remission, the patient was readmitted with severe psychotic symptoms, including agitation, delusions, and behavioral disorganization. Neuroimaging demonstrated a stable post-inflammatory lesion without signs of active inflammation. Treatment required individualized polypharmacotherapy, with careful monitoring of extrapyramidal and endocrine adverse effects. This case highlights the complex interaction between autoimmune neuroinflammation, hormonal dysregulation, and psychiatric manifestations. Early recognition, comprehensive immunological and endocrine evaluation, and long-term multidisciplinary follow-up are essential to optimize outcomes and reduce relapse risk in autoimmune neuropsychiatric syndromes.